Early Post-Registry Experience With Drug-Eluting Stents in the Superficial Femoral Artery. (February 2016) - Wooster, Mathew; Dansey, Kirsten; Shames, Murray
Objective: Restenosis remains the primary failure mode after stent placement in the superficial femoral artery (SFA). Drug-eluting technology aims to reduce intimal hyperplasia and subsequent stent failure, improving durability for endovascular management of SFA occlusive disease. We present our early experience with the Cook Zilver PTX stent. Methods: We retrospectively reviewed a prospectively collected database of patients undergoing placement of the Cook Zilver PTX stent for SFA or popliteal disease since its availability to our institution in October 2013. Patients treated with additional non-PTX stents were excluded. Patient demographics, comorbidities, concomitant procedures, TASC classification, procedural details, and follow-up were reviewed. Results: Thirty-one limbs in 30 patients were treated with Zilver PTX stents, 5 limbs were excluded for concomitant use of non-PTX stents, leaving 26 limbs in 26 patients for analysis. Indications for intervention were claudication in 17 (65.4%), rest pain in 1 (3.8%), and tissue loss in 8 (30.8%). A median of 2 PTX stents per limb was used to treat a mean length of 14.2 ± 11 cm with technical success of 100%. Concomitant inflow (N = 4) or atherectomy (N = 2) interventions were performed in 23%. Sixty-nine percent of lesions were TASC C (N = 7) or D (N = 11) and 42% were total occlusions. Over a mean 20-week follow-up, 2 occlusions were noted (mean 27 weeks), one was treated with surgical bypass and the other with endovascular salvage. Limb salvage in the series was 92.3% with 2 patients requiring major amputations for infected, non-healing wounds, despite patent stents. Conclusion: On mean 20-week follow-up, we have seen 92.3% primary patency and 96.2% secondary patency. A larger number of patients and longer follow-up will be required to determine the true real-world efficacy of this drug-eluting device, but early experience is encouraging and warrants continued trial.